Obstetric outcome in pregnancies with borderline versus normal amniotic fluid index - Augustine, Tony; Palakkan, Saphina; N., Umadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Amniotic fluid is an indicator of placental function on the fetal development. It is regulated by several systems, including transmembraneous pathway, fetal production (fetal urine and lung fluid) and uptake (fetal swallowing), and the balance of fluid movement via osmotic gradients. The amniotic fluid index is the most commonly used method of measuring amniotic fluid. An AFI between 5 to 8 cms is borderline oligohydraminos. To compare the fetal and maternal outcome in pregnancies with borderline amniotic fluid index (5 to 8 cms) and normal AFI. Methods: This prospective cohort study was carried out on 94 pregnant patients attending the antenatal clinic of MES Medical College, Perinthalmanna between January 1st and December 31st 2016. Women with a singleton pregnancy in the third trimester were enrolled into the study. Of these 47 cases were in the normal AFI group and 47 cases in the borderline group. Adequate information was obtained from the patient’s medical record and the groups were compared on maternal and fetal complications. Results: The study results showed that more cases with borderline AFI had their non stress test to be nonreactive (59.6% versus 23.4%) and was associated with more fetal heart rate abnormalities (51% versus 17%). The number of meconium stained amniotic fluid (48.9% versus 19.1%) and caesarean deliveries (51.1% versus 21.2%) were also more among the borderline group. Conclusions: Findings indicated that there are more adverse fetal and maternal outcome among the borderline AFI group.